RESTORATIVE JUSTICE SEBAGAI LANGKAH MENUJU PENEGAKAN HUKUM PIDANA MODERN DAN BERKEADILAN - Abeth, Hendrich Juk (STIH Awang Long Samarinda, 2017)
Although in the positive law in Indonesia the process of settlement of criminal cases can not be completed outside the court does not mean that in certain cases not possible implementation. Restorative Justice is a process of settlement that is conducted outside the criminal justice system by involving victims, erpetrators, families of victims and perpetrators, communities, and parties with an interest in a crime committed to reach an agreement. In this case the criminal justice process focused on criminal prosecution is transformed into a process of dialogue and mediation to create an agreement on a more fair and balanced criminal prosecution for the perpetrator and the victim.